2008
DOI: 10.1111/j.1468-2982.2008.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs on Calcium Currents Recorded from Cortical and PAG Neurons: Therapeutic Implications for Migraine

Abstract: Cortex and periaqueductal grey (PAG) play a major role in the pathophysiology of migraine. Some antiepileptic drugs (AEDs) influence the activity of these structures by modulating high-voltage-activated (HVA) Ca(2+) channels and are effective in migraine prevention. The aim of the present study was to investigate the expression of total HVA Ca(2+) channels in cortical and PAG neurons and to study the differential action of AEDs on these channels. Isolated neurons were visually identified based on morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…LEV was reported to inhibit Ca V 2.2 and Ca V 2.1 (P/Q type) subunits (Surges et al, 2008). In general, such effects were measured in response to shortterm LEV application and were reported to produce small irreversible reductions in Ca 2ϩ current (Lukyanetz et al, 2002;Pisani et al, 2004;Costa et al, 2006;Martella et al, 2008); our data, which showed no short-term LEV effects, are in disagreement with those studies. However, Niespodziany et al (2001) investigated the time dependence of LEV effects on Ca V channels, and their finding that LEV required Ն30 min of perfusion to cause significant inhibition correlates well with our data.…”
Section: Tablecontrasting
confidence: 57%
See 1 more Smart Citation
“…LEV was reported to inhibit Ca V 2.2 and Ca V 2.1 (P/Q type) subunits (Surges et al, 2008). In general, such effects were measured in response to shortterm LEV application and were reported to produce small irreversible reductions in Ca 2ϩ current (Lukyanetz et al, 2002;Pisani et al, 2004;Costa et al, 2006;Martella et al, 2008); our data, which showed no short-term LEV effects, are in disagreement with those studies. However, Niespodziany et al (2001) investigated the time dependence of LEV effects on Ca V channels, and their finding that LEV required Ն30 min of perfusion to cause significant inhibition correlates well with our data.…”
Section: Tablecontrasting
confidence: 57%
“…Although LEV did not affect Na ϩ -and low-voltageactivated Ca V channels (Zona et al, 2001), it was reported to inhibit high-voltage-activated Ca V channels; those effects occurred in response to short-term LEV application (Lukyanetz et al, 2002;Pisani et al, 2004;Costa et al, 2006;Martella et al, 2008), although one study reported that LEV action on Ca V channels required prolonged exposure . LEV inhibition of delayed rectifier K ϩ channels also was reported (Madeja et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The increased iron deposition in the PAG supported the possibility of repeated activation (chronic daily headache) of the antinociceptive network (Del Rio and Linera 2004). Activation of the PAG was blocked by a triptan (Bartsch et al 2004;Jeong et al 2008), and antiepileptic drugs which are effective in migraine might modulate the function of PAG neurones (Martella et al 2008). Patients with familial hemiplegic migraine carry mis-sense gene (CACNA1A) mutations which encode the a1A subunit of the voltagegated Ca 2?…”
Section: Higher Brainstem Nucleimentioning
confidence: 99%
“…Topiramate is a sulphamate-substituted monosaccharide derived from D-fructose (Privitera, 1997;Shank and Maryanoff, 2008;Edvinsson and Linde, 2010) and is commonly used to treat epilepsy (Langtry et al, 1997;Privitera, 1997) and migraine (Storey et al, 2001;Adelman et al, 2008;Edvinsson and Linde, 2010;Linde et al, 2013). The use of topiramate for these clinical applications seems to reside in its ability to selectively decrease CNS neuronal activity via inhibition of certain neuronal Ca 2+ channels (Martella et al, 2008) as well as to modulate central glutamate and GABA signaling (White et al, 2000;Edvinsson and Linde, 2010). When used as monotherapy, placebo-subtracted weight loss induced by topiramate typically ranges between 3.8% and 6.5% depending on the dose (Aronne et al, 2013).…”
Section: F Phentermine and Topiramate (Qsymia)mentioning
confidence: 99%